SPORTS JOURNALISM AND MEDIA RESEARCH - Velizar Sredanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Communicology theoreticians, sociologists, and sports experts strive to explain significance of sport, power and influence of media (TV in particular) and sports journalism through analysis of media and viewers. Phenomena observed on number of football (soccer) and Olympic games through a prism of media research of the Television of Montenegro.